FREQUENCY AND CLINICAL SPECTRUM OF MULTIDRUG RESISTANT ACINETOBACTER BAUMANNII AS A SIGNIFICANT NOSOCOMIAL PATHOGEN IN INTENSIVE CARE UNIT PATIENTS - Sana, Fatima; Hussain, Ashfaq; Hussain, Wajid; Zaman, Gohar; Abbas, Muhammad Waqas; Imtiaz, Anam; Satti, Luqman (Journal of Ayub Medical College Abbottabad, 2021)
Background: Acinetobacter baumannii has emerged as one of the leading causes of multidrug resistant nosocomial infections worldwide. It is able to survive in hospital environment and build up diverse resistance mechanisms making it difficult to treat with current antibiotics. Objective: It was to determine the frequency and patterns of Acinetobacter baumannii in intensive care units (ICU) settings. Methods: A cross sectional study was carried out in the Department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi, from 1st July 2017 to 30th June 2019. A total of 603 non-duplicate clinical specimens were received from intensive care units. Specimens yielding growth of multidrug resistant Acinetobacter baumannii, were evaluated as per standard protocol. The antimicrobial sensitivity testing was performed as per Clinical and Laboratory Standard Institute guidelines (2017-2018). Results: Among Acinetobacter baumannii (310 isolates), 5% were multidrug resistant, 93% extensively drug resistant and 1% pan drug resistant. Percentage of carbapenem resistant strains was 92%. In drugs like tigecycline and polymyxin, resistance was noted as 73% and 1% respectively. High yield of this superbug was mainly obtained from respiratory specimens (43.5%), whereas 24% were detected from wound infections and 29% from other samples. Conclusion: This study showed a rapidly increasing resistance in Acinetobacter baumannii. Therefore, polymyxin remains the only option in our intensive care units, but its usage as empirical therapy in our setting has led to the emergence of resistance to this drug. Implementing infection control practices, antimicrobial stewardship and restricted use of polymyxin can play a significant role in reducing health care burden.